Bangladesh - Non-Lending Technical Assistance on Capital Markets - World Bank (Washington, DC, 2013)
The Bangladesh stock market experienced significant volatility in late 2010 and early 2011 which took stock values high above fundamentals and threatened the stability of the financial system. This note takes a systematic look at the capital markets underpinnings in Bangladesh, including the regulatory framework, the rule-making bodies and enforcement issues. It also addresses systemic weaknesses responsible for market instability which was observed at the end of 2010 and early 2011. The note analyses the outlines specific areas of potential vulnerabilities of securities markets, as assessed against appropriate practice guidelines for stability, sustainability, transparency, and enforcement. A plan of action going forward is also suggested. This note draws on a considerable amount of prior analytical work. Bangladesh capital markets remain ineffective. The government debt securities markets are illiquid preventing the Bangladesh financial system from relying on a market-based yield curve. Bangladesh has yet to develop an active money market. Trading of treasury bills in the secondary market is limited because these instruments, along with treasury bonds, make up the statutory liquidity reserve and are therefore generally held until maturity by commercial banks and other financial institutions. Trading is also thin in repurchase agreements, for two main reasons. First, commercial banks have a weak treasury function, and most do not actively manage liquidity. Second, there is no standard master repurchase agreement, a gap that should be addressed to support orderly development of the repo market.